UMPSA treats the people of Dolokgede Village, Bojonegoro, Indonesia through the UMPSA Foundations ASEAN Exploration Adventure programme - Nur Izzaty Fatihah, Nazar (UMPSA, 2023)
DOLOKGEDE, 16 November 2023 – 14 volunteers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) together with 15 volunteers from Universitas Bojonegoro (UNIGORO), IKIP PGRI Bojonegoro and Universitas Nahdlatul Ulama Sunan Giri (UNUGIRI) successfully completed the ASEAN Exploration Adventure programme in Bojonegoro, Indonesia.